2013
DOI: 10.1172/jci66387
|View full text |Cite
|
Sign up to set email alerts
|

Giant axonal neuropathy–associated gigaxonin mutations impair intermediate filament protein degradation

Abstract: Giant axonal neuropathy (GAN) is an early-onset neurological disorder caused by mutations in the GAN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
157
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(175 citation statements)
references
References 79 publications
14
157
0
Order By: Relevance
“…It is a predicted E3 ligase adaptor protein believed to flag substrates for ubiquination on the proteasome 17 . Recent studies also suggest that disturbed cytoskeletal regulation, likely involving the proteasome degradation pathway 18 , is responsible for the formation of aggregates of some type 3 and type 4 intermediate filament proteins, which is a morphological characteristic of this disease, and many others.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is a predicted E3 ligase adaptor protein believed to flag substrates for ubiquination on the proteasome 17 . Recent studies also suggest that disturbed cytoskeletal regulation, likely involving the proteasome degradation pathway 18 , is responsible for the formation of aggregates of some type 3 and type 4 intermediate filament proteins, which is a morphological characteristic of this disease, and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Using three cellular models, Mahammad et al 18 showed that restoring functional gigaxonin in cultured cells had a direct impact on vimentin, peripherin and NF-L. Using GAN patient fibroblasts, they were able to clear the vimentin aggregates by expressing wild type (WT) gigaxonin.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations